Consumer Insight During Covid-19: Understanding the Influence of Price Saving Benefits, Time Saving Benefits, and Food Safety Risk Perception To Consumer Intention On Online Food Delivery - Nadlifatin, Reny; Rahmanqa, Alifio; Razif, Mohammad; Persada, Satria Fadil (Jurnal Manajemen Teknologi, 2023)
Abstract. Technology has a significant impact on human existence, particularly in the phenomenon of online food delivery services. Every year, this makes online food shopping more appealing to the public. The study's goal is to compare consumers' willingness to use online meal delivery services during the Covid-19 pandemic to the new normal. The research methodology employed in the study was multivariate Structural Equation Modeling (SEM). Price savings benefits, time savings benefits, and food safety risk perceptions are all considered crucial and relevant in influencing customer intentions. The relevant data was acquired from online meal delivery customers by 299 data during the survey stage. A Google form was used to conduct the survey online. The Partial Least Square SEM approach will be utilized for the data analysis calculation stage. The findings of this investigation reveal three established hypothetical links. Data analysis revealed that Food Safety Risk Perception has a negative and significant impact on customer intentions. Customers' intentions are positively influenced by the Price Saving Benefit and the Time Saving Benefit is revealed to be the highest beta value. This study also discusses theoretical and practical contributions. Keywords: Online food delivery, price saving benefits, time saving benefits, food safety risk perceptions, consumer intention Abstrak. Teknologi memiliki dampak yang signifikan terhadap keberadaan manusia, khususnya dalam fenomena layanan pengiriman makanan. Setiap tahun, ini membuat belanja makanan online lebih menarik bagi masyarakat umum. Tujuan studi tersebut adalah membandingkan keinginan konsumen untuk menggunakan layanan pesan antar makanan online di masa pandemi Covid-19 dengan kenormalan baru. Metodologi penelitian yang digunakan dalam penelitian ini adalah multivariat Structural Equation Modeling (SEM). Manfaat penghematan harga, manfaat penghematan waktu, dan persepsi risiko keamanan pangan semuanya dianggap penting dan cukup relevan dalam memengaruhi niat pelanggan. Data yang relevan diperoleh dari pelanggan pengiriman makanan online dengan jumlah 299 data selama tahap survei. Formulir Google digunakan untuk melakukan survei online. Pendekatan SEM Partial Least Square akan digunakan untuk tahap perhitungan analisis data. Temuan penyelidikan ini mengungkapkan tiga hubungan hipotetis yang mapan. Analisis data mengungkapkan bahwa Persepsi Risiko Keamanan Pangan memiliki dampak negatif dan signifikan terhadap niat pelanggan. Niat pelanggan dipengaruhi secara positif oleh Price Saving Benefit dan Time Saving Benefit ditemukan sebagai nilai beta tertinggi. Studi ini juga membahas kontribusi teoritis dan praktis. Kata kunci: Pengiriman makanan online, manfaat penghematan harga, manfaat penghematan waktu, persepsi risiko keamanan pangan, niat konsumen